Developing extreme-value instructional material based on model eliciting activities - Dinal Ulya Sukiman; Darmawijoyo Darmawijoyo Darmawijoyo; Somakim Somad Somad (Jurnal Kependidikan, 2018)
PENGEMBANGAN BAHAN AJAR NILAI EKSTRIM BERBASIS MODEL ELICITING ACTIVITIESAbstrakPenelitian ini bertujuan untuk menghasilkan bahan ajar nilai ekstrim yang didesain dengan enam prinsip model eliciting activities (MEAs) yakni reality, model construction, self-assesment, model documentation, construct shareability, re-useability, dan effective prototype. Penelitian ini adalah penelitian design research tipe development study (development research) menggunakan model pengembangan analysis, design, develompment, implementation, dan evaluation (ADDIE) dan dievaluasi dengan tahapan formative evaluation (one to one, small group, dan field test). Subjek penelitian adalah siswa kelas XI IPA 1 SMA Negeri 2 Palembang yang berjumlah 40 orang. Hasil penelitian menunjukkan bahwa bahan ajar nilai ekstrim berbasis MEAs berupa Lembar Kerja Siswa (LKS) dan Petunjuk Guru (PG) yang valid, praktis, dan mudah digunakan. Perangkat pembelajaran ini membantu siswa memahami konsep turunan dan nilai ekstrim serta menerapkan konsep tersebut ke dalam permasalahan nyata (real life problem) dan menarik minat serta keseriusan siswa untuk belajar nilai ekstrim dan mengeksplorasi kemampuan matematis siswa tersebutAbstractThis study was aimed at generating a set of extreme-value instructional materials using six principles of the model eliciting activities (MEAs) namely reality, model construction, self-assessment, model documentation, construct shareability and re-useability, and effective prototype. The study used the research development model using the analysis, design, development, implementation, and evaluation (ADDIE) model and was evaluated using formative evaluation phases (one to one, small group, and field test). The subjects were 40 students in grade XI of the Natural Science Department of the State Senior High School 2, Palembang. The result is a set of instructional design consisting of lesson plans, student worksheets, and teacher guides which are valid, practical, and easy-to-use. This instructional material is able to help students to understand the concept of derivatives and extreme values and apply the concepts to real-life problems. It also attracts the interest and the seriousness of the students to learn extreme values and explore their mathematical abilities.